KESELAMATAN KERJA : SYSTEMATIC LITERATURE REVIEW (SLR) DAN ANALISA BIBLIOMETRIK - Prilatama, Aris; Sopiah (Transpublika Publisher, 2023)
The purpose of this study is to analyze the application of occupational safety in various working environments and conditions. The method used in this study is the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analyses) method and Bibliometric analysis using VosViewer. Sources of data obtained from Scopus and Taylor & Francis for the 2017-2022 period. The results of 136 journals were obtained, then data reduction was carried out using inclusion and exclusion criteria, 34 journals were obtained which would be reviewed. The results of this study indicate that the application of work safety will be very effective if you always follow and adapt to technological developments and the times.